The hydrodynamical analysis of working capacity plug-forming armatures - V. N. Sharifullin; A. V. Sharifullin (Известия высших учебных заведений: Проблемы энергетики)
The mathematical model of non-stationary hydrodynamical process in a gas main, arising is constructed at closing a latch. Mathematical modelling transitive hydrodynamical process for cases of full and incomplete closing a latch is lead. On the basis of results of modelling it is offered, as an attribute of a degree of blocking of a stream a latch, to use growth rate of pressure in a pipe before a latch.